Fostering Students’ Critical Awareness of Social Issues Under the Principles of Freire’s Problem-Posing Education (2020)
ABSTRACT: This action research project aimed at fostering students’ critical awareness of social issues through the implementation of Freire’s problem-posing principles in an English class. For the purpose of this study, suicide was the social issue addressed. Data were collected by means of different instruments such as surveys, students’ artifacts, journals, recordings, class activities and informal conversations. Students were exposed to different activities for six weeks which were developed following the cycle of reflection and action proposed by Wallerstein and Auerbach (2004). After the analysis, the findings showed that lessons framed within problem posing permit learners to become more aware of social issues and promote learners’ interaction and participation in the EFL class.